Current Epidemiological Characteristics of Imported Malaria, Vector Control Status and Malaria Elimination Prospects in the Gulf Cooperation Council (GCC) Countries - Jamshaid Iqbal; Suhail Ahmad; Ali Sher; Mohammad Al-Awadhi (Microorganisms, 2021)
Malaria is the most common vector-borne parasitic infection causing significant human morbidity and mortality in nearly 90 tropical/sub-tropical countries worldwide. Significant differences exist in the incidence of malaria cases, dominant Plasmodium species, drug-resistant strains and mortality rates in different countries. Six Gulf Cooperation Council (GCC) countries (Bahrain, Kuwait, Qatar, Oman, Saudi Arabia and United Arab Emirates, UAE) in the Middle East region with similar climates, population demographics and economic prosperity are aiming to achieve malaria elimination. In this narrative review, all studies indexed in PubMed describing epidemiological characteristics of indigenous and imported malaria cases, vector control status and how malaria infections can be controlled to achieve malaria elimination in GCC countries were reviewed and discussed. These studies have shown that indigenous malaria cases are absent in Bahrain, Kuwait, Qatar and UAE and have progressively declined in Oman and Saudi Arabia. However, imported malaria cases continue to occur as GCC countries have large expatriate populations originating from malaria-endemic countries. Various malaria control and prevention strategies adopted by GCC countries including more stringent measures to reduce the likelihood of importing malaria cases by prior screening of newly arriving expatriates and vector elimination programs are likely to lead to malaria elimination in this region.